1977
DOI: 10.1002/jbm.820110104
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein and fatty acid adsorption on platelet adhesion and aggregation at the blood–polymer interface

Abstract: Thrombus formation on a foreign surface is a complicated process, involving many factors. However, there is little doubt that a foreign surface adsorbs plasma proteins upon blood contact and that the nature of this adsorbed layer may determine the mechanism of platelet adhesion and aggregation. The adhesion and aggregation of platelets play an important role in the initial events of thrombus formation on a foreign surface. In this work, adsorption studies using human blood plasma were done on several polymer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Other studies reported in the literature on adsorption from plasma are those of Kim et al (19), Kochwa The majority of these studies used an approach similar to that taken in the present work, i. e. they focrrsed on the behavior of a few major proteins usually by trace h6sting. Kim et al (19) studied the adsorption of albu-in, fibrinogen and y-gtobulin on a group of hydrophobic surfac€s. Kinetics over a 3-hr period were "conventional" for all systerrrs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies reported in the literature on adsorption from plasma are those of Kim et al (19), Kochwa The majority of these studies used an approach similar to that taken in the present work, i. e. they focrrsed on the behavior of a few major proteins usually by trace h6sting. Kim et al (19) studied the adsorption of albu-in, fibrinogen and y-gtobulin on a group of hydrophobic surfac€s. Kinetics over a 3-hr period were "conventional" for all systerrrs.…”
Section: Discussionmentioning
confidence: 92%
“…However, comprehensive studies using plasma or blood ircelf as the adsorbate are less common. From data so far published using plasma as the bulk medium (18)(19)(20)(21) it appears that different behavior is to be expected in the more complex media. For saample the studies of Vroman et al (2L) suggest that the adsorbed layer composition will change with time in a plasma medium.…”
Section: !Ntroductionmentioning
confidence: 99%
“…Clearly, interactions between the implant surface and the host must be of predominant importance, and these events are likely initiated by surface--protein adsorption . Implantable biomaterials are spontaneously covered by a layer of host proteins within seconds after contact with body fluids (55)(56)(57)(58)(59). These adsorbed proteins gradually change conformation and become irreversibly adsorbed (24,31,32,(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the plasma concentrations of albumin, y-globulin, and fibrinogen was 50:10:3; however, higher amounts of y-globulin and fibrinogen were used in the mixture as reported elsewhere (19). Albumin, y-globulin, and fibrinogen are the major plasma proteins and had been chosen for investigation of their role in the calcification process.…”
Section: In Vitro Calcification Experimentsmentioning
confidence: 99%